2012
DOI: 10.1007/s00404-012-2591-0
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant histone acetylation and methylation levels in woman with endometriosis

Abstract: Aberrant histone modification may play an important role in the pathogenesis of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…The precise mechanisms were unknown. In some transforming conditions, such as thyroid tumor and endometriosis, different acetylation of histone H3 and H4 occurred separately during transformation [29,30]. We considered that T-cell leukemia and B-cell leukemia might show different acetylation of histones during development of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms were unknown. In some transforming conditions, such as thyroid tumor and endometriosis, different acetylation of histone H3 and H4 occurred separately during transformation [29,30]. We considered that T-cell leukemia and B-cell leukemia might show different acetylation of histones during development of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 It was recently shown that different types of lesions vary in the expression of HDACs 56,57 and that tissues (lesions and endometrium) from patients have different levels of H3K9 and H4K16 acetylation compared to control tissues. 58,59 Thus, evidence has started to accumulate that endometriotic lesions have a characteristic histone code and that global H3 and H4 acetylation within promoter regions of candidate genes is differentially modulated in lesions.…”
Section: Recommendation (New)mentioning
confidence: 99%
“…6,29,68,69 A recent study that compared global H3 and H4 acetylation status and H3K4 and H3K9 methylation in lesions versus endometrium from healthy women showed what can be perceived as different results from those presented here; however, data sets are difficult to compare due to lack of detail in technical and analytical methods as well as due to differences in the reference group. 40 A study by Munro et al investigated the global histone acetylation levels in normal endometrium during the menstrual cycle. 31,70 They reported that acetylation levels of some but not all histone acetylation marks were increased in the early proliferative phase and/or during the window of implantation, when active transcription of genes would be expected.…”
Section: Waf1/cip1mentioning
confidence: 99%
“…[35][36][37][38][39] However, very few studies have been conducted on endometriosis in this regard. 40 As a first step in dissecting the role of this epigenetic mechanism in endometriosis, we quantified the global acetylation levels of H3 and H4 in ectopic and eutopic endometrial tissues from patients with and without endometriosis. We hypothesized that lesions will have globally deacetylated histones.…”
Section: Waf1/cip1mentioning
confidence: 99%